Implementasi Program Jaminan Kestabilan Harga Komoditi Pertanian (JASKOP) dalam Upaya Stabilitas Pangan di Desa Bulan-Bulan Kabupaten Batu Bara - Chairunnisa Dalimunthe; Muhammad Imanuddin Kandias Saraan (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2026)
Red chili price fluctuations in Bulan-Bulan Village, Batu Bara Regency, encouraged the North Sumatra Provincial Government to introduce the Agricultural Commodity Price Stability Guarantee Program (JASKOP) through Governor’s Decree No. 188.44/749/KPTS/2025, with the Solar Dryer Dome (SDD) as its main postharvest instrument. This study examines the gap between the program design and its field implementation and analyzes its contribution to food stability. A descriptive qualitative approach was employed using in-depth interviews, observations, and document analysis. Informants included provincial government officials, an agricultural extension worker, farmer-group administrators, beneficiary farmers, and a representative of PT Dhirga Surya. Data were analyzed using Grindle’s implementation framework covering policy content, implementation context, and outcomes. The findings show that eight of the nine implementation indicators were not optimal, while compliance and responsiveness performed relatively well. Physical infrastructure, administrative legitimacy, and farmer acceptance were available; however, integrated operating procedures, working capital, cold storage, marketing contracts, and the legal basis for appointing a regional enterprise as an offtaker remained incomplete. Consequently, routine production, changes in marketing practices, and increased farmer income had not materialized. JASKOP therefore remains in transition from infrastructure development to full operation and has not yet achieved comprehensive food stability.